Quantum confinement and interface structure of Si nanocrystals of sizes 3–5 nm embedded in a-SiO2 - Lioudakis, Emmanouil; Othonos, Andreas S.; Hadjisavvas, George C.; Nassiopoulou, Androula Galiouna; Kelires, Pantelis C. (My University, 2007)
Spectroscopic ellipsometry and Monte Carlo simulations are employed to answer the fundamental question whether the energy gaps of Si nanocrystals with sizes in the range of 3–5 nm, which are embedded in amorphous silica, follow or deviate from the quantum confinement model, and to examine their interfacial structure. It is shown that the optical properties of these nanocrystals are well described by the Forouhi–Bloomer interband model. Analysis of the optical measurements over a photon-energy range of 1.5–5 eV shows that the gap of embedded nanocrystals with a mean size of 3.9 nm follows closely quantum confinement theory. A large band gap expansion (0.65 eV) compared to bulk Si is observed. The Monte Carlo simulations reveal a non-abrupt interface and a large fraction of interface oxygen bonds. This, in conjunction with the experimental observations, indicates that oxygen states and the chemical disorder at the interface have a negligible influence on the optical properties of the material in this size regime.
Keywords: Monte Carlo simulations; Silicon nanocrystals; Spectroscopic ellipsometry; Optical properties